Interactive Learning Media for Dance Work Creation with The Development of "Montro Dance Movements" for Arts and Culture Lessons - Haryanti, Haryanti; Hendri, Zulfi (West Science Social and Humanities Studies, 2025)
This research is developmental research that aims to: (1) determine the production procedure, (2) determine the characteristics, and (3) analyze the feasibility of interactive media for creating dance works by developing "Montro dance movements" for arts and culture lessons. The development model used in this research refers to the Borg and Gall development model, which consists of nine stages: 1) analysis of potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, 7) product revision, 8) usage trial, and 9) product revision. The characteristics of interactive media for creating dance works with the development of "Montro dance movements" developed in this study consist of six learning activities with the syntax of the Project Based Learning (PjBL) learning model and are equipped with images, animations, videos, and reflection sheets. Based on the results of the media expert validation test, the score was 3.85 on a Likert scale of 4, the results of the material expert validation test were 3.9 on a Likert scale of 4, and the results of the language expert validation test were 4 on a Likert scale of 4. Based on the suggestions and input of the experts, design revisions were made. Product trials were conducted by 5 teachers from 4 different schools in the Bantul area, namely SMAN 1 Dlingo, SMAN 1 Pajangan, SMAN 1 Bambanglipuro, and SMAN 3 Bantul. Product trials were also conducted by 10 students of SMAN 1 Banguntapan. Based on the teacher's assessment, the score was 3.78 on a Likert scale of 4 and the ideal percentage was 94%. The results of the product trials to teachers were included in the "Very Good" category. Based on student assessments in the product trial, a score of 3.38 was obtained on a Likert scale of 4 and an ideal percentage of 84.5%. Suggestions and input from teachers were used to revise the product. The product trial was conducted at SMAN 1 Banguntapan with 35 grade XI students. Based on student assessments, a score of 3.42 was obtained on a Likert scale of 4 and an ideal percentage of 85.5%. The results of the product usage test were included in the "Very Good" category. Based on the results of the usage test, no revisions were made.